Social justice and the experiences of people with mild learning difficulties who are looking for paid work - Tarlo, Ruth (2021)
People with mild learning difficulties who are not eligible for adult social care are largely absent from research about employment and unemployment. Policy discussions about supporting disabled people into employment also tend to overlook people with mild learning difficulties, either assuming that they are not disabled at all or that the barriers they face are the same as for other disabled people. This thesis challenges those assumptions by focusing on the stories of people with mild learning difficulties who were looking for work. These stories were gathered through multiple interviews and observations guided by a narrative research methodology, a social model view of disability and a commitment to social justice. The research explored the assumptions underpinning government policy towards the employment of disabled people, focusing on the period from 2010 to 2019, and the implications for people with mild learning difficulties. It highlighted how government policy towards promoting the employment of disabled people had been inadequate and unjust, with detrimental effects for people with mild learning difficulties, particularly by miscategorising disability as an individual characteristic and over-individualising responsibility for employability. The thesis draws on Fraser’s social justice concepts of participatory parity, maldistribution and misrecognition (Fraser, 2001) to analyse participants’ stories of unemployment and employment, and their relationship to notions of disability. It concludes that people with mild learning difficulties face a range of “structurally-produced injustices” (Fraser, 2012:45) in their relationships with the paid labour market, through inadequate and sometimes counterproductive support, insufficient income and disrespect that too easily slides into exploitation or abuse. The thesis highlights evidence of multi-faceted injustices, arising from the interactions of the participants with the welfare state and the labour market. Aspects of these injustices, which demand to be addressed for their own sake, also have relevance to a much larger section of the population who work in low paid, precarious work and/or claim social security benefits.